Versões do patrimônio: usos e narrativas dos moradores do Poço da Draga - Firmino, Raniery Fontenele (2013)
This research starts with a reflection on the draft decree no 3.551 establishing the record of cultural immaterial nature of the Brazilian cultural patrimony and that, somehow, it has been extending the meaning of the patrimony category. So, this dissertation investigated the construction process of the social reality of what comes to be constituted and defined as significant cultural patrimony, having as reference the processes for grabs control of the area around the historic center of Fortaleza-CE. It took specifically as empirical field for anthropological analysis and understanding the case of residents Poço da Draga who have resided in the neighborhood Centro for over 70 years. The category of patrimony here is thought ethnologically with reference to the views of residents, their uses and their narratives in the space the neighborhood Centro.This research starts with a reflection on the draft decree no 3.551 establishing the record of cultural immaterial nature of the Brazilian cultural patrimony and that, somehow, it has been extending the meaning of the patrimony category. So, this dissertation investigated the construction process of the social reality of what comes to be constituted and defined as significant cultural patrimony, having as reference the processes for grabs control of the area around the historic center of Fortaleza-CE. It took specifically as empirical field for anthropological analysis and understanding the case of residents Poço da Draga who have resided in the neighborhood Centro for over 70 years. The category of patrimony here is thought ethnologically with reference to the views of residents, their uses and their narratives in the space the neighborhood Centro.